Three‐dimensional transthoracic echocardiographic identification of individual cusps of the pulmonary valve: Potential misidentification by the two‐dimensional technique. Issue 6 (2nd June 2018) - Elsayed, Mahmoud; Hsiung, Ming C.; Nanda, Navin C.; Alratroot, Ahmad; Turaga, Naga Sai Shravan
Abstract : We demonstrate the incremental value of live/real time three‐dimensional transthoracic echocardiography (3DTTE) over the two‐dimensional modality in the identification of all three cusps of the pulmonary valve in patients in whom only two leaflets could be detected by the latter technique. This was because of the ability of 3DTTE to view the cusps enface permitting assessment of relationship to one another and the surrounding cardiac structures. In addition, 3DTTE showed not only the potential errors that can occur in pulmonary valve cusp identification when the two‐dimensional modality is used alone but also how some of these errors can be avoided by paying attention to the surrounding structures.